Current Population Survey: Voter Supplement File, 1986 ([Verlag nicht ermittelbar], 1987)
This collection provides information on labor force activity for the week prior to the survey. Comprehensive data are available on the employment status, occupation, and industry of persons 14 years old and over. Also supplied are personal characteristics such as age, sex, race, marital status, veteran status, household relationship, educational background, and Spanish origin. In addition to these standard data, the November voting and registration supplement contains data pertaining to citizenship status, voting status in the election of November 4, 1986, and registration status. Telephone availability data are also provided in this file.